2001
DOI: 10.1074/jbc.m009287200
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Determinants of Coenzyme Specificity in Ferredoxin-NADP+ Reductase by Site-directed Mutagenesis

Abstract: On the basis of sequence and three-dimensional structure comparison between Anabaena PCC7119 ferredoxin-NADP ؉ reductase (FNR) and other reductases from its structurally related family that bind either NADP ؉ /H or NAD ؉ /H, a set of amino acid residues that might determine the FNR coenzyme specificity can be assigned. These residues include Thr-155, Ser-223, Arg-224, Arg-233 and Tyr-235. Systematic replacement of these amino acids was done to identify which of them are the main determinants of coenzyme specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
94
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(99 citation statements)
references
References 60 publications
5
94
0
Order By: Relevance
“…We conclude from these data that Leu-76, Leu-78, and Val-136 of Anabaena FNR are not critical residues for complex formation and ET between NADPH and FNR. This was expected since the region where NADP(H) binds to FNR is different from the area where the mutations were introduced (24,50,51).…”
Section: Discussionmentioning
confidence: 99%
“…We conclude from these data that Leu-76, Leu-78, and Val-136 of Anabaena FNR are not critical residues for complex formation and ET between NADPH and FNR. This was expected since the region where NADP(H) binds to FNR is different from the area where the mutations were introduced (24,50,51).…”
Section: Discussionmentioning
confidence: 99%
“…This structural and sequence similarity study (8) assigned PDR to a distinct family of flavoprotein reductases, all related to ferredoxin-NADP ϩ reductase (FNR). Medina et al (21) studied coenzyme specificity in FNR and found the amino acid residues involved. None of those residues are found in the reductase components shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…-4.2 (Liang et al 2007) P. stipitis XR 1K8C (h) K270R, N272D 2.9 9.3 -1.2 (Maddock et al 2015) E. coli CaADH 1KEV (h) G198D, S199V, P201E, Y218A >1 ? -4.6 (Maurer et al 2005) B Log Relative Activity c (Medina et al 2001) A. PCC7119 FDNR 2BSA S223D 0.12 8.1x10 3 -5.4 (Nakanishi et al 1997) M. musculus CR 1CYD T38D 31 1.3x10 3 -0.51 (Paladini et al 2009 (Schepens et al 2000) S. bicolor MDH 7MDH (1CIV) G84D, S85I, R87Q, S88A 12 2.1x10 4 -0.96 (Scrutton et al 1990) E. coli GTR 1GET A179G, A183G, V197E, R198M, K199F, H200D, R204P 8.1 1.8x10 4 -1.5 (Shiraishi et al 1998) N. crassa CbR S920D, R932S 65 7.2x10 4 -2.6 (Takase et al 2014) S. sp. A1-R 3AFN H37N, G38S, R39H, K40V, A41D >1 ?…”
mentioning
confidence: 99%